Dynamic mechanical and thermal shock characteristics of NiCoCrAlY/YSZ composite coatings - Chia, Chee Tat. (2008)
Plasma sprayed thermal barrier coatings are used extensively in dynamic environment which are exposed to noise and vibration. Economic, building efficient and lightweight reasons have encouraged the increased use of vibration damping materials compared to the alternative of component redesign and retrofit. Therefore, it is important to understand the dynamic mechanical properties of coatings as well, which will be used in the dynamic conditions. An added motivation would be that the damping measurement allowed insight into the rate parameters governing the kinetics of various internal transport processes.